2012
DOI: 10.1002/pd.3975
|View full text |Cite
|
Sign up to set email alerts
|

Experts' opinions on the benefit of an incidental prenatal diagnosis of sex chromosomal aneuploidy: a qualitative interview survey

Abstract: Most experts favored an incidental prenatal diagnosis of SCA despite the complex counseling issues and their acknowledgment of possible parental decisions to terminate pregnancy. They believed the benefits greatly outweigh the disadvantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…This raises ethical and practical challenges for expanding the indications for cfDNA testing to SCAs and other conditions such as microdeletions or microduplications, since the related biological aspects will lead to complex counseling issues. However, a qualitative interview survey of experts' opinions on the incidental prenatal diagnosis of SCAs shows that their early detection has benefits greatly exceeding counseling issues and possible parental decisions to terminate the pregnancy [19]. Recent findings also show positive effects of postnatal hormone therapy on the behavioral phenotype if applied earlier to these patients [20,21].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…This raises ethical and practical challenges for expanding the indications for cfDNA testing to SCAs and other conditions such as microdeletions or microduplications, since the related biological aspects will lead to complex counseling issues. However, a qualitative interview survey of experts' opinions on the incidental prenatal diagnosis of SCAs shows that their early detection has benefits greatly exceeding counseling issues and possible parental decisions to terminate the pregnancy [19]. Recent findings also show positive effects of postnatal hormone therapy on the behavioral phenotype if applied earlier to these patients [20,21].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…While Turner and Klinefelter syndromes are frequently associated with clinical manifestations and phenotype stigmata, 47,XXX, 47,XYY, and mosaic forms of SCAs have a much less effect on intelligence, fertility, sexual development, and phenotype than was presumed earlier [8]. A qualitative interview survey of experts' opinion on incidental prenatal diagnosis of SCAs reported that it is believed that early detection of SCAs has benefits that greatly exceed the complex counseling issues and possible parental decisions to terminate the pregnancy [21]. Presymptomatic detection of SCAs may provide an opportunity for early interventions toward the better quality of life of the affected child and a chance for the parents and the child to adapt to the diagnosis and possible repercussions that it represents [20].…”
Section: Introductionmentioning
confidence: 99%
“…4 As most of these conditions are not associated with structural abnormalities identifiable by ultrasound or abnormal biochemical profiles, their detection previously has been limited to the postnatal setting or as a consequence of invasive fetal testing for other conditions. 5 The most common SCAs include Monosomy X (Turner syndrome), XXY or XXYY (Klinefelter syndrome), XXX (Triple X syndrome or Trisomy X), and XYY. Most cases of XXX and XYY are phenotypically mild without intellectual disability and therefore may never warrant clinical evaluation.…”
Section: Introductionmentioning
confidence: 99%